Atypical presentation of dengue fever - Dutta, Sanjeev; Khullar, Niharika (International Journal of Contemporary Pediatrics, 2025)
We are reporting two cases with atypical presentation of dengue fever. Acute pancreatitis following dengue fever is a rare complication, it has been reported in critical phase of illness (5-10 days of illness). Dengue fever can present as asymptomatic state to hemorrhagic fever with shock. Authors report a case of acute pancreatitis in early phase of dengue fever on day 1 of illness. A 4-year-old male child who presented with fever, severe abdominal pain, nausea and vomiting. Laboratory tests revealed increased serum amylase and serum lipase levels (3 times the upper normal limit), anemia, normal platelet counts, dengue NS1 positive and dengue IgM and Ig G negative. Lobar pneumonia in dengue fever is not reported in literature. A 9-year-old male child presented with complaints of fever and cough for 8 days, abdominal pain and vomiting for 2days. Dengue Ig M and Ig G were positive. CECT chest was done which showed large area of consolidation with air bronchogram, and centrilobular nodules in left upper lobe, s/o Lobar pneumonia. Bilateral ground glass opacities seen. Bronchoscopy was done, brocho alveolar lavage (BAL) showed normal study, no malignant cells, no atypical organism isolated. BAL GeneXpert for TB was negative. BAL aerobic culture showed no growth.